Optimalisasi E-Govenrment dan E-Office Birokrasi dalam Mewujudkan Smart City Menuju Pemerintahan Modern - Bambang Agus Diana; Benny Sigiro; Vigilia K. Montolalu (Program Studi Administrasi Negara Universitas Serang Raya, 2024)
Public management and bureaucracy are both inseparable and closely related to managing, organizing and running government activities and public services. Along with the concept of smart city (smart city) which refers to the management of governance that applies technology by integrating various aspects of urban life, modern ICT-based governance and innovative public sector management approaches (bureaucracy) are demands to improve efficiency, effectiveness, transparency and accountability. This requires the implementation and development of e-government and e-office as part of realizing the goals of bureaucratic reform. This paper is intended to examine the e-government and e-office bureaucracy in realizing the concept of smart city in governance and public services. The writing method used is literature study. Optimization of e-government and e-office becomes very important as an integral part of the realization of the smart city concept. As many districts / cities in Indonesia have implemented smart cities, and according to their plans and achievement targets for 2015-2045. Human resources support, development of facilities and infrastructure, as well as infrastructure, which is not just the existence of a number of applications created in the administration of government and public services but better and Real services can be obtained online and perceived quickly, easily, precisely and responsively according to the needs of the community.